Simultaneous separation, concentration and determination of trace fluoroquinolone antibiotics in environmental samples using a polymer aqueous two‐phase system coupled with HPLC. Issue 9 (24th June 2019) - Sun, Zhuo; Lu, Yang; Zhu, Lina; Liu, Wei; Qu, Yue; Lin, Nan; Yu, Ping
Abstract: BACKGROUND: Fluoroquinolone antibiotics and their metabolites can accumulate in soil and water. Trace amounts of fluoroquinolone antibiotic residues in the environment necessitate the pretreatment of samples prior to analysis. In this work, a polyoxyethylene cetyl ether (POELE20)–NaH2 PO4 aqueous two‐phase system (ATPS) was combined with high‐performance liquid chromatography (HPLC) to separate and determine trace quantities of ciprofloxacin (CIP), norfloxacin (NRF) and pefloxacin (PEF) in environmental samples. RESULTS: Single‐factor, multi‐factor, reproducibility and accuracy experiments were performed. The extraction efficiencies and enrichment factors for the three antibiotics were above 90 and 13.8%, respectively, under optimal conditions. The recovery efficiency of CIP was 92.08–99.50%, with a relative standard deviation (RSD) of 0.60–6.34%, and the recovery efficiency of NRF and PEF was 93.40–99.30%, with RSD of 0.98–5.16%, when this method was applied to spiked water and soil samples. The RSDs of intra‐ and inter‐day analyses were 1.56–3.42 and 1.33–3.97%, respectively. CONCLUSIONS: This study demonstrated that POELE20–NaH2 PO4 ATPS coupled with HPLC was suitable for the simultaneous separation, concentration and determination of trace quantities of CIP, NRF and PEF in environmental samples. Moreover, this method can be applied for the determination of trace fluoroquinolone antibiotics in food samples. © 2019 Society of Chemical Industry